Voices from the heart : four centuries of American piety - Lundin, Roger; Noll, Mark A., 1946- (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 1987)
Includes diaries, letters, sermons, poems, stories, novels, political treatises, and autobiographies. Authors include Jonathan Edwards, John Winthrop, Anne Bradstreet, Martin Luther King, Jr., Charles Finney, Walter Rauschenbusch, Nathaniel Hawthorne, Abraham Lincoln, John Updike, Thomas Merton, Flannery O'Connor, Harriet Beecher Stowe, Frederick Douglass, William Faulkner, Reinhold Niebuhr, Emily Dickinson, Woodrow Wilson, among others.
Sermon and speech / John Winthrop -- Excerpt from Of Plymouth plantation / William Bradford -- Letter to his fellow missionaries / Jean de Brebeuf -- Selected letters / Marie of the incarnation -- Excerpt from "Helps to Preserve Spiritual Health and Cheerfulness" / Roger Williams -- Autobiographical excerpt / Thomas Shepherd -- Selections from his last will and testimony / Obadiah Homes -- "The Flesh and the Spirit" / Anne Bradstreet -- "Verses upon the Burning of Our House, July 10th, 1666" / Anne Bradstreet -- "As Weary Pilgrim, Now at Rest / Anne Bradstreet -- Captivity narrative / Mary Rowlandson -- "Meditation 8, on John 6:51: I am the living bread" / Edward Taylor -- "The preface" / Edward Taylor -- "Huswifery" / Edward Taylor -- Personal narrative / Jonathan Edwards -- Spiritual travels / Nathan Cole -- Journal entries / David Brainerd -- Journal entries / John Woolman -- Journal entries / Esther Edwards Burr -- Diary entries and selected letters / Francis Asbury -- Journal Entries / Henry Alline -- Excerpts from "Joy in the Holy Spirit" / Timothy Dwight -- Selections from his memoirs / Charles G. Finney -- "Holy Living" (from The way of life) / Charles Hodge -- "The interior of a heart" (from The scarlet letter) / Nathaniel Hawthorne -- Excerpt from The way of holiness / Phoebe Palmer -- Narrative excerpt / G.W. Offley -- Selected documents / Abraham Lincoln -- Selected letters / C.F.W. Walther -- "The martyr" (from Uncle Tom's cabin) / Harriet Beecher Stowe -- Appendix to his narrative / Frederick Douglas -- "The sermon" (from Moby Dick) / Herman Melville -- "Safe in their alabaster chambers" / Emily Dickinson -- "I reckon - when I count at all" / Emily Dickinson -- "The brain - is wider than the sky" / Emily Dickinson -- "Behind me - dips eternity / Emily Dickinson -- "This world is not conclusion" / Emily Dickinson -- "The Bible is an antique volume" / Emily Dickinson -- Selected stories / Dwight L. Moody -- Excerpts from "The little office of the Holy Ghost" (from A sodality manual) / John Joseph Keane -- An address on the Bible / Woodrow Wilson -- Excerpt from Prayers of the social awakening / Walter Rauschenbusch -- Excerpt from "The heart that dared not let in the sun" (from Giants in the earth) / Ole Rolvaag -- Excerpt from The meaning of prayer / Harry Emerson Fosdick -- Reverend Shegog's sermon (from The sound and the fury) / William Faulkner -- Excerpts from Leaves from the notebook of a tamed cynic / Reinhold Niebuhr -- "The gift of the treasure" (from Treasure in clay) / Fulton J. Sheen -- Selected columns / Dorothy Day -- "Following hard after God" (from The pursuit of God) / A.W. Tozer -- Excerpt from While it is day / Elton Trueblood -- Selected letters / Francis Schaeffer -- "Together" (from A man called Peter) / Catherine Marshall -- Prose Excerpts / Thomas Merton -- "The Fear of death and the hope of the resurrection" / Edward John Carnell -- Selected letters / Flannery O'Connor -- Excerpt from The sacred journey / Frederick Buechner -- Excerpt from No graven image / Elisabeth Elliot -- "I have a dream" / Martin Luther King, Jr. -- "Who is in control?" / Howard Rienstra -- "Inside the walls" (from Life sentence) / Charles Colson -- Excerpt from Gracias! a Latin American journal / Henri Nouwen -- "Lifeguard" / John Updike -- Excerpt from Christ the tiger / Thomas Howard -- "A Hand in the Wound" / Virginia Stem Owens.
Includes bibliographical references.
Keywords: Christian literature, American; Piety